(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this experimental study is to investigate the behaviour of cantilever walls that are strengthened by bonding of steel channels. Three, cantilever wall test specimens were constructed and tested under cyclic lateral loading. For this experimental research three wall specimens were strengthened with different steel channels. The different configurations of steel channels were considered the channel at bottom, lateral channel and the combination of both lateral and vertical channels. All steel strip configurations are arranged on one side of the wall. Test results showed that the channel at bottom configurations improved the lateral strength, energy dissipation capacity and deformation capacity of the cantilever wall significantly. Nominal flexural strength developed by strengthened specimens, and hence, the observed maximum base shear was controlled by flexure. As cantilever wall fails due to overturning movement we attached a steel L-channel at junction of stem and base of slab. Steel channels limited the opening of shear cracks and improved the lateral displacement capacity. Using ANSYS the Finite element modeling is carried out for numerical analysis. In this Present work, we have observed that when applied pressure increases then there is an increase in maximum deformation and equivalent stresses. It is observed that for a single brick wall and double brick wall of various dimensions, increase in applied pressure increases the maximum deformation and also equivalent stresses.